Measurement of ω meson production in pp collisions at √s = 13 TeV - Acharya, S.; Adamovã, D.; Agarwal, A.; Aglieri Rinella, G.; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; et al. (Springer Science and Business Media Deutschland GmbH, 2025)
The pT-differential cross section of ω meson production in pp collisions at √s = 13 TeV at midrapidity (|y| < 0.5) was measured with the ALICE detector at the LHC, covering an unprecedented transverse-momentum range of 1.6 < pT < 50 GeV/c. The meson is reconstructed via the ω → π+π−π0 decay channel. The results are compared with various theoretical calculations: PYTHIA8.2 with the Monash 2013 tune overestimates the data by up to 50%, whereas good agreement is observed with Next-to-Leading Order (NLO) calculations incorporating ω fragmentation using a broken SU(3) model. The ω/π0 ratio is presented and compared with theoretical calculations and the available measurements at lower collision energies. The presented data triples the pT ranges of previously available measurements. A constant ratio of Cω/π0 = 0.578 ± 0.006 (stat.) ± 0.013 (syst.) is found above a transverse momentum of 4 GeV/c, which is in agreement with previous findings at lower collision energies within the systematic and statistical uncertainties.
Keywords: Hadron-Hadron Scattering, Particle and Resonance Production, QCD; https://purl.org/pe-repo/ocde/ford#1.03.03